Study of D-limonene as novel green hydraulic fracturing surfactant in shale gas reservoir - Krishnan, A. (Elsevier B.V., 2022)
This study focuses on rock-fluid interaction during hydraulic fracturing in shale gas reservoir. Hydraulic fracturing is a well stimulation technique used to create fracture network in reservoirs by connecting the main planar hydraulic fracture with the pre-existing natural fracture. Hydraulic fracturing fluid additives such as surfactants are added into the hydraulic fracturing fluid system to enhance oil and gas productivity by assisting fluid recovery after fracturing. The main objective of this study is to evaluate the effectiveness and formation damage parameters of the proposed novel green surfactant as hydraulic fracturing fluid additive where commercial-chemical based surfactant was studied for comparison purpose. The green surfactant used was D-limonene whereas Sodium Alpha Olefin Sulfonate (AOS) was used as commercial-chemical based surfactant. Thermogravimetric analysis (TGA) was done to ensure the D-limonene can withstand the high reservoir temperature in which the D-limonene had inflection point and onset temperature of 410 °C and 380 °C respectively. Soaking test was then conducted where the shale samples were soaked in hydraulic fracturing fluid for seven days. The outcome of the soaking test was then studied in Scanning Electron Microscopy (SEM) and wettability analysis. The SEM test showed that the average pore size of the soaked shale samples were similar to the original shale sample which indicated minimal to no formation damage caused by the hydraulic fracturing fluid. Besides that, the contact angle test resulted in the distilled water and D-limonene forming a contact angle of 90° and 0° respectively on the shale samples. The AOS formed contact angles between 65° and 75° for the tested concentrations. From the results, the shale sample was found to be oil wet and showed a high affinity towards the D-limonene followed by AOS and distilled water. Higher affinity of the surfactants promoted the desorption of the hydraulic fracturing fluid from the shale surface. © 2022 Elsevier B.V.